Wykorzystanie koncepcji „funkcji miejsca” w badaniach wielofunkcyjności obszarów wiejskich (przykład gminy miejsko-wiejskiej Rzgów w powiecie wschodnio-łódzkim) = Application of the sense of place concepts in the analysis of rural areas multifunctional development (case study of Rzgów, łódzki-wschodni poviat) - Suliborski, Andrzej (IGiPZ PAN, 2015)
The article concerns the area of urban and rural commune of Rzgów, which neighbours Łódź in the south. The main aim of the research is the application of the “function of the place” conception and its empirical particularisation in the analyses of a specific multipurpose rural area located within the suburban area of a large city. The function of the place conception constitutes a platform of integration between the functional, morphological and humanistic approaches at the level of individual settlement. The category of place, interpreted from the viewpoint of people’s needs, and not only the economic and spatial dimensions of localisation seems to be in this case of key importance. This conception does not only aim at ordering and determining the research procedure, but also plays a heuristic role, i.e. it supports discovering facts and connections between them, which in turn leads to formulating explanations and new hypotheses. Ordering of the research procedure with reference to the commune’s area under analysis requires identification of three main aspects (dimensions) of place’s function: its form, exploitation and social meaning. The research has been conducted from three spatial perspectives: local (the area of commune), meso-regional (the agglomeration of Łódź) and macro-regional (Poland). The author has paid particular attention to the local scale – the commune of Rzgów within its administrative boarders. The conclusions reached, refer to the research subject itself (Poland), yet they are also theoretical in character. A commune is a dynamic place and due to ongoing processes can be divided into subareas (rural and urbanised rural). Two groups of functions – allochtonic and autochtonic – play a decisive role is these transformations. The former has had an influence on the establishment of urban (the town of Rzgów) and urbanised rural places. The latter, on the other hand, decides upon formation of multipurpose places with strong rural attributes.
Keywords: sense of place concept; multifunctionality; rural areas